Motivasi Petani Dalam Usaha Tani Asparagus (Kasus Anggota Kelompok Tani Mertanadi di Desa Pelaga, Kecamatan Petang, Kabupaten Badung) - PRATAMA, I PUTU YOGA; ASTITI, NI WAYAN SRI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Farmer Motivation In Asparagus Farms (Case Of Mertanadi Group Member  In Pelaga Village, Sub District Petang, Badung District) Pelaga Village is one of the villages in Bali where most of the population work in agriculture. One of the crops that arecultivated in this village is asparagus. No studyhas investigated the level of motivation of farmers in cultivating asparagus in this village. This study aims to understand this. The study was conducted specifically on Mertanadi farmer groups that was determined through purposive method. The study involved 38 farmer respondents that were determined by using the Slovin formula. This study shows that the motivation level of farmers in cultivating asparagus is high with a score of 3,68. Intrinsic motivation is high with a score of 3,82 and extrinsic motivation is also high with a score of 3,54. The result shows that in the intrinsic factors, there are indicators with low category, namely the need for appreciation. Farmers must focus on cultivating asparagus plants so that they can meet their needs and their families’ so that they get appreciation from fellow groups and the government. In the extrinsic factors there are also indicators with low categories, namely indicators of other farmers. Farmers should cooperate with each other so that they can motivate each other to improve the continuity of the cultivation of asparagus in the future.